Comparative Study on the Design of Elevated Rectangular and Circular Concrete Water Tanks (2012)
Reinforced concrete overhead water tanks are used to store and supply safe drinking water. Design and cost estimation of overhead water tanks is a time consuming task, which requires a great deal of expertise. This study therefore examines the efficiency of Rectangular and Circular tanks. Tanks of 30m3, 90m3, 140m3 and 170m3 capacities were used in order to draw reasonable inferences on tank’s shape design effectiveness, relative cost implications of tank types and structural capacities. Limit state design criteria were used to generate Microsoft Excel Spreadsheet Design Program, named MESDePro for quick and reliable design. The basic tank’s construction materials- steel reinforcement, concrete and formwork were taken-off from the prepared structural drawings. Results of the material take-offs showed that, for each of the shapes, the amount of each structural materials increase as the tank capacity increases. Also Circular-shaped tank consumed lesser individual material as compared to Rectangular ones. Hence, this will give Circular-shaped tanks a more favoured selection over the rectangular shaped tanks.